2021
DOI: 10.1021/acs.est.1c05726
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mass Spectrometry Screening of Emerging Organophosphate Esters (OPEs) in Wild Fish: Occurrence, Species-Specific Difference, and Tissue-Specific Distribution

Abstract: There is a dearth of information regarding the pollution status of emerging organophosphate esters (OPEs) in wild fish. Here, we optimized and validated a quick, easy, cheap, effective, rugged, and safe (QuEChERS) pretreatment method, which was further applied for target, suspect, and nontarget screening of OPEs in n = 48 samples of wild fishes from Taihu Lake (eastern China). This integrated technique allows us to fully identify 20 OPEs, and 9 out of them are emerging OPEs detected in wild fish for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…For emerging tri-OPEs, higher DFs were found for bisphenol-A bis­(diphenyl phosphate) (BPA-BDPP), bis­(3-isopropylphenyl)­phenyl phosphate (B3IPPPP), and 3- tert -butylphenyl diphenyl phosphate (3tBPDPP) in CSF (8.3, 9.0, and 13%) than in serum (1.7, 0, and 6.3%) in our study. Previous studies have also reported the presence of BPDP and IPDP in the brain tissue of silver carp and IDPP and tris­(isopropyl-phenyl) phosphate (IPPP) in the brain tissue of dolphins . These findings suggest that these novel aryl-tri-OPEs may penetrate the BBB and cause neurotoxicity, which needs to be verified.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…For emerging tri-OPEs, higher DFs were found for bisphenol-A bis­(diphenyl phosphate) (BPA-BDPP), bis­(3-isopropylphenyl)­phenyl phosphate (B3IPPPP), and 3- tert -butylphenyl diphenyl phosphate (3tBPDPP) in CSF (8.3, 9.0, and 13%) than in serum (1.7, 0, and 6.3%) in our study. Previous studies have also reported the presence of BPDP and IPDP in the brain tissue of silver carp and IDPP and tris­(isopropyl-phenyl) phosphate (IPPP) in the brain tissue of dolphins . These findings suggest that these novel aryl-tri-OPEs may penetrate the BBB and cause neurotoxicity, which needs to be verified.…”
Section: Resultsmentioning
confidence: 89%
“…One previous study reported the existence of several tri-OPEs in the brain tissue of dolphins from the Alboran Sea, Spain and showed that TCIPP [median: 41.2 ng/g dry weight (dw)] and TNBP (18.3 ng/g dw) exhibited higher concentrations than TCEP, EHDPP, TMPP, and TBOEP (0.71–4.69 ng/g dw), results that were consistent with higher proportions of TCIPP and TBP in CSF in this study. However, different phenomena were observed in another two research studies, one of which reported higher concentrations of TBOEP [10 ng/g wet weight (ww)] than TNBP (2.20 ng/g ww), TCIPP (0.776 ng/g ww), TCEP (0.246 ng/g ww), and EHDPP (0.178 ng/g ww) in the brain tissue of silver carp from Taihu Lake and the other showed more accumulation of chlorinated tri-OPEs (TCIPP, TCEP, and TDCIPP) in mouse brain tissue than TNBP, TIBP, and TPHP after 72 days of inhalation exposure . Exposure differences may help to explain the discrepancies among these studies.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results highlighted the negative effects of TDCIPP on the skeletal system of fish. Considering the high detection frequency of TDCIPP in aquatic systems, , the environmental risks of TDCIPP to aquatic organisms warrant further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the concentrations of TDCIPP were up to 251 ng/g lw in catfish ( Claris fuscus , from Pearl River Delta, China), 140 ng/g lw in perch ( Perca fluviatilis , from Lake Djupasjön, Sweden), 16.6 ng/g lw in walleye ( Sander vitreus , from Lake Erie, United States) . The concentrations of TDCIPP in wild crucian carp ( Carassius auratus ) were 44.6 ng/g lw in Beiyun River, China, 23.7 ng/g lw in Jinjiang River, China, and 0.118 ± 0.182 ng/g ww in TaiHu Lake, China . These monitoring data elucidated the ubiquitous presence of TDCIPP in aquatic environments, which led to increasing concerns of its environmental risks, especially for fish.…”
Section: Introductionmentioning
confidence: 99%